Pharmacokinetics and preliminary efficacy of two vaginal gel formulations of ultra-low-dose estriol in postmenopausal women. (3rd March 2016) - Delgado, J. L.; Estevez, J.; Radicioni, M.; Loprete, L.; Moscoso del Prado, J.; Nieto Magro, C.
Abstract: Objectives To investigate the pharmacokinetics, safety and preliminary effectiveness of ultra-low-dose estriol vaginal gel formulations (20 μg/g (T1) and 50 μg/g (T2)) compared to Ovestinon® (estriol 500 μg/0.5 g (R)) and placebo in postmenopausal women. Methods Forty-three volunteers were randomly assigned to received T1, T2, R or placebo once daily for 21 days. Absorption of estriol after single and multiple administration was analyzed. Cytological changes in the vagina, tolerability and safety were also investigated. Results Thirty-six women were included in the pharmacokinetic analysis. Systemic absorption was lower with test formulations (AUC0- t : 171.65 ± 80.18 (T1) and 406.75 ± 199.53 (T2) pg/ml × h) than with Ovestinon® (1221.97 ± 549.06 pg/ml × h). Estriol exposure of the test formulations after multiple administration (AUCss : 36.33 ± 30.52 (T1) and 73.71 ± 46.86 (T2) pg/ml × h) was significantly lower than after single-dose administration and not significantly different between them. In contrast, the exposure after repeated administration of Ovestinon® was considerable and not statistically different from levels after single administration. All estriol formulations produced similar improvement in the vaginal maturation value, while placebo showed a small and not significant change. Overall safety and acceptability were good. Conclusions Estriol 20 and 50 μg/g formulations, while showing a comparable capacity for reversing vaginal atrophy, present a highly favorable safety profile, producing a very low systemic absorption of estriol and significantly lower than that of Ovestinon®.